Peran Penting Public Relations Di Era Digital - Arini Ulfa Satira; Rossa Hidriani (Sadida Islamic Communications and Media Studies, 2021)
This article discusses the important role of Public Relations in the Digital Age. The method of analysis of this article is a literature study with a descriptive qualitative analysis approach. Digital Public Relations can be referred to as Cyber Public Relations which is used in company reputation management. The practice of Digital Public Relations is part of public relations activities adapted from the use of information and communication technology for companies. PR plays an important role in providing healthy and positive information to the public in the midst of the polemic of the development of communication technology. Therefore, PR must provide information that takes into account pluralism and cultural sensitivity in the community.